2002
DOI: 10.1046/j.1523-1755.62.s82.4.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II regulates the synthesis of proinflammatory cytokines and chemokines in the kidney

Abstract: Ang II in vivo increases TNF-alpha production in the kidney. Ang II also up-regulates other proinflammatory mediators, including IL-6, MCP-1 and NF-kappaB, coincidentally associated to the presence of glomerular and interstitial inflammatory cells in the kidney. All these data further strengthen the idea that Ang II plays an active role in the inflammatory response in renal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
316
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(328 citation statements)
references
References 41 publications
5
316
0
7
Order By: Relevance
“…14,15 Studies in hypertensive individuals have shown increased plasma and vascular tissue levels of C-reactive protein (CRP) and several inflammatory cytokines, suggesting a potential association between vascular inflammation and hypertension. [16][17][18][19] Although the evidence for a direct relationship between salt intake and BP is basically established, [20][21][22][23] the clinical evidence is not adequate to consider whether this effect translates into increased incidence of cardiovascular diseases independent from BP in patients with high dietary salt consumption. In this study, we hypothesized that dietary salt intake may be related with inflammation and albuminuria independently from BP in non-diabetic hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Studies in hypertensive individuals have shown increased plasma and vascular tissue levels of C-reactive protein (CRP) and several inflammatory cytokines, suggesting a potential association between vascular inflammation and hypertension. [16][17][18][19] Although the evidence for a direct relationship between salt intake and BP is basically established, [20][21][22][23] the clinical evidence is not adequate to consider whether this effect translates into increased incidence of cardiovascular diseases independent from BP in patients with high dietary salt consumption. In this study, we hypothesized that dietary salt intake may be related with inflammation and albuminuria independently from BP in non-diabetic hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Studies in hypertensive individuals have shown increased plasma and vascular tissue levels of C-reactive protein (CRP) and several inflammatory cytokines, suggesting a potential association between vascular inflammation and hypertension. [16][17][18][19] Although the evidence for a direct relationship between salt intake and BP is basically established, 20-23 the clinical evidence is not adequate to consider whether this effect translates into …”
mentioning
confidence: 99%
“…In kidney and other organs, AngII stimulates expression of proinflammatory mediators, including growth factors, cytokines and chemokines, and adhesion molecules (10,11). Infusion of AngII into rats causes inflammatory cells to invade the glomeruli and interstitium (12)(13)(14). In addition, inflammatory cells can themselves produce AngII, generating a positive feedback loop that perpetuates the inflammatory response and progressive renal injury (15).…”
mentioning
confidence: 99%
“…The diverse effects of angiotensin II on the kidney include 1) promotion of glomerular capillary hypertension due to efferent arteriole vasoconstriction (20,21), 2) stimulation of transforming growth factor-β (TGF-β) production by mesangial cells and tubular epithelial cells (22)(23)(24), 3) stimulation of matrix protein synthesis (23), 4) interstitial fibrosis (25,26), 5) mesangial cell growth (27,28), 6) changes of tubular epithelial cell phenotype and tubulointerstitial cell kinetics (29), 7) cytokine release from renal cells (30), and 8) activation of nuclear factor-κB (NF-κB) and increased monocyte chemoattractant protein-1 (MCP-1) gene expression on mesangial cells, leading to macrophage infiltration (10,31,32). These actions of angiotensin II are known to be the common pathway for several types of renal injury.…”
Section: Discussionmentioning
confidence: 99%